Transcending attitudes: teacher responses to professional development in trauma-informed education - Stacy A. Gherardi; Allison Stoner (Springer, 2024)
Abstract The adoption of trauma-informed practices in schools is a significant and growing area of school reform efforts. It has been assumed that professional development aimed at influencing teacher attitudes toward trauma-informed care in schools is an important first step in adopting trauma-informed practices and improving student and school outcomes. However, there are gaps in the literature assessing the impact of trauma-informed professional development on teacher attitudes toward trauma-informed care, and there is little evidence linking changes in teacher attitudes to changes in practices. This exploratory study assessed teacher responses to a year-long pilot program providing intensive professional development and consultation on trauma-informed practices in one urban elementary school in the U.S. Southwest. Findings raise questions about the impact of professional development on teacher attitudes and subsequent changes to practice.